2005
DOI: 10.1038/sj.jea.7500460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrafine and fine particulate and gaseous air pollution on cardiac autonomic control in subjects with coronary artery disease: The ULTRA study

Abstract: Previous studies have shown an association between elevated concentrations of particulate air pollution and cardiovascular morbidity and mortality. Therefore, the association between daily variation of ultrafine and fine particulate air pollution and cardiac autonomic control measured as heart rate variability (HRV) was studied in a large multicenter study in Amsterdam, the Netherlands, Erfurt, Germany, and Helsinki, Finland. Elderly subjects (n=37 in Amsterdam, n=47 in both Erfurt and Helsinki) with stable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 36 publications
7
120
1
Order By: Relevance
“…This was particularly true for PM 2.5 although evidence of non-linearity was also observed for UFPs and BC. The multi-centre ULTRA study found that equivalent increases in fine PM could be positively associated with HRV, but not in each of its sites with equivalent increases which suggests that effects may differ according to the sources of PM at a particular site (14). While findings have not been consistent in previous studies, a strong and consistent increase in HRV in association with fine PM (but not gaseous co-pollutants also measured) has been observed among healthy young men, suggesting increased vagal activity possibly due to a local inflammatory reaction in the lungs (15).…”
Section: Discussionmentioning
confidence: 94%
“…This was particularly true for PM 2.5 although evidence of non-linearity was also observed for UFPs and BC. The multi-centre ULTRA study found that equivalent increases in fine PM could be positively associated with HRV, but not in each of its sites with equivalent increases which suggests that effects may differ according to the sources of PM at a particular site (14). While findings have not been consistent in previous studies, a strong and consistent increase in HRV in association with fine PM (but not gaseous co-pollutants also measured) has been observed among healthy young men, suggesting increased vagal activity possibly due to a local inflammatory reaction in the lungs (15).…”
Section: Discussionmentioning
confidence: 94%
“…More recent studies have implicated other components of PM with reductions in both respiratory and cardiovascular health (Delfino et al 2004;2005;Timonen et al 2006;Beelen et al 2008), as well as increased mortality (Ostro et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 pollution is particularly harmful since it can penetrate human bronchi and lungs owing to the small particle size 9 . Hence, long-term exposure to PM 2.5 increases morbidity and mortality [10][11][12][13][14] . Recently, there have been serious PM pollution problems in developing countries with a large manufacturing industry such as China.…”
mentioning
confidence: 99%